Diabetes Insipidus in A 8-Year Old Balinese Boy - AAN Prayoga; IN Westra; Sudaryat Suraatmadja (Indonesian Pediatric Society Publishing House, 2018)
We report a case of diabetes insipidus in a 8 years old Balinese boy. The diagnosis was based on clinical features, laboratory findings, and a good result to chlorpropamide therapy. Common differential diagnoses, i.e., were hypercalcemia, potassium deficiency, psychogenic polydipsia, and diabetes mellitus, could be excluded. The treatment of first choice for diabetes mellitus is desmopressin acetate; however, since the drug was not available, we gave chlorpropamide instead. The patient responded well to 125 mg of clorpropamide twice daily.